Phylogenetic relationships and evolutionary patterns of the genus Psammolestes Bergroth, 1911 (Hemiptera: Reduviidae: Triatominae) - Hernández, Carolina; Alvarado, Mateo; Salgado-Roa, Fabian C.; Ballesteros, Nathalia; Rueda-M, Nicol; Oliveira, Jader [UNESP]; Alevi, Kaio Cesar Chaboli [UNESP]; da Rosa, Joao Aristeu [UNESP]; Urbano, Plutarco; Salazar, Camilo; Ramírez, Juan David (Springer Nature, 2022)
Background: The evolutionary history of biodiversity in South America has been poorly studied in the seasonal dry tropical forest (SDTF). Species diversification in this ecosystem may have a twofold explanation. First, intermittent connections in the middle and late Pleistocene promoted species dispersal and/or genetic connectivity between lineages isolated in disjunct patches of forest. Second, allopatric speciation proceeded immediately after the formation and colonization of the SDTF in the Neogene. Here we studied the diversification of Psammolestes, a genus endemic of the SDTF and naturally infected with Trypanosoma cruzi (agent of Chagas disease), using a combination of phylogenetic, population genetics and niche model methods, and evaluated the reliability of the three morphospecies currently recognized. Results: Our multilocus analyses recovered P. coreodes and P. tertius in a monophyletic clade sister to P. arthuri. Species delimitation tests recovered these lineages as different species despite the shared genetic variation observed between P. coreodes and P. tertius in five genes. Also, genetic variation of the genus clustered in three groups that were consistent with the three morphospecies. Our demographic model predicted a scenario of divergence in absence of gene flow, suggesting that mixed haplotypes may be the result of shared ancestral variation since the divergence of the subtropical-temperate species P. coreodes and P. tertius. In contrast, the tropical species P. arthuri was highly differentiated from the other two in all tests of genetic structure, and consistently, the Monmonier’s algorithm identified a clear geographical barrier that separates this species from P. coreodes and P. tertius. Conclusions: We found three genetically structured lineages within Psammolestes that diverged in absence of gene flow in the late Miocene. This result supports a scenario of species formation driven by geographical isolation rather than by divergence in the face of gene flow associated with climatic oscillations in the Pleistocene. Also, we identified the Amazon basin as a climatic barrier that separates tropical from subtropical-temperate species, thus promoting allopatric speciation after long range dispersion. Finally, each species of Psammolestes occupies different climatic niches suggesting that niche conservatism is not crucial for species differentiation. These findings influence the current vector surveillance programs of Chagas disease in the region.
Keywords: Niche divergence; Phylogenetic; Population genetics; Psammolestes; Rhodniini; Seasonal dry tropical forest; Triatominae